Design, synthesis and molecular modeling studies of few chalcone analogues of benzimidazole for epidermal growth factor receptor inhibitor in search of useful anticancer agent. (April 2016) - Chhajed, Santosh S.; Sonawane, Sandeep S.; Upasani, Chandrashekhar D.; Kshirsagar, Sanjay J.; Gupta, Pramodkumar P.
Graphical abstract: Abstract: In the present investigation, few 3-(substitutedphenyl)-1-[2-(1-hydroxy-ethyl)]-1 H -benzimidazol-1-yl)prop-2-en-1-ones are EGFR antagonist are designed, by molecular docking analysis. The synthesized compounds were tested for their in vitro anticancer activity by propidium iodide fluorescent assay and Trypan blue viability assay against colorectal cancer cell lines (HCT116) and non-small cell lung cancer cell lines (H460). Human Epithelial Kidney cell lines (HEK) are used as normal cell lines for studying effect of drug on non-cancerous cells within human body. Evaluation of cytotoxic studies of synthesized compounds CHL(1–8) reveal that compound CHL1 [IC50 = 7.31 and 10.16 μM against HCT116 and H460 cell lines respectively, by PI assay] and CHL8 [IC50 = 12.52 and 6.83 against HCT116 and H460 μM cell lines respectively] possess promising cytotoxic activity.